2011
DOI: 10.1177/0013161x11404219
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Effects of Principal–Student Discussions on Eighth Grade Students’ Gains in Reading Achievement

Abstract: Purpose: School effectiveness and instructional leadership research over the past 30 years has largely concluded that principal effects on student achievement are small and indirect. It has been assumed that the principal effect is important but mediated through other school factors. Findings: This experimental study found that one-on-one discussions between a principal and a nonproficient student that focused on the student's 2008 reading score and a goal for his or her 2009 reading score had a direct and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 23 publications
(40 reference statements)
0
24
1
1
Order By: Relevance
“…In this changing policy context, some scholars asserted that school accountability policies were transforming instructional leadership from an option into a necessity. This was certainly the case in the USA (Murphy 2008;Nettles and Herrington 2007;Schoen and Fusarelli 2008;Silva et al 2011).…”
Section: Global Policy Trendsmentioning
confidence: 95%
See 2 more Smart Citations
“…In this changing policy context, some scholars asserted that school accountability policies were transforming instructional leadership from an option into a necessity. This was certainly the case in the USA (Murphy 2008;Nettles and Herrington 2007;Schoen and Fusarelli 2008;Silva et al 2011).…”
Section: Global Policy Trendsmentioning
confidence: 95%
“…America's new accountability-oriented frameworks placed responsibility for student learning results squarely on the shoulders of principals (Hallinger 2011b;Hallinger and Murphy 2012;Neumerski 2012;Nettles and Herrington 2007;Leithwood 2001;Schoen and Fusarelli 2008;Silva et al 2011). This, for example, resulted in policies that mandated comprehensive systems of teacher and principal training and evaluation that raised the bar in terms of standards of performance (Leithwood 2001;Murphy and Shipman 2003;Silva et al 2011). Race to the Top mandated the replacement of principals (and teachers) in schools that fail to demonstrate annual improvements in learning results for students.…”
Section: Global Policy Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayrıca bu çalışmada sadece dolaylı ilişkiler incelenmiştir. Bazı araştırmacılar, okul müdürünün öğrencilerle birlikte çalışma yaparak onların başarılarını doğrudan etkilediğini gösterir kanıtlar sunmuştur (Gentilucci ve Muto, 2007;Silva, White ve Yoshida, 2011). Bu kapsamda okul müdürü ile öğrenci başarısı arasındaki doğrudan ilişkiyi inceleyen çalışmalar tasarlanabilir.…”
Section: öNerilerunclassified
“…Studies have found that positive, focused, one-on-one interactions between student and principal have been shown to have positive implications on student cognitive achievements (Silva, White, & Yoshida, 2011). Jane's students met with their principals on a small scale, within a positive context, bound by a focused topic-changing policy.…”
Section: Students' Affective Growth In New and Challenging Experiencesmentioning
confidence: 99%